2016
DOI: 10.1111/asj.12701
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fatty acid transport protein 1 on proliferation and differentiation of porcine intramuscular preadipocytes

Abstract: Fatty acid transport protein 1 (FATP1) plays an important role in the fatty acid transmembrane transport and fat deposition. However, its role in porcine intramuscular preadipocytes proliferation and differentiation remain poorly understood. Here, we examined the effects of pFATP1 on porcine intramuscular preadipocytes proliferation and differentiation. Overexpression of pFATP1 in porcine intramuscular preadipocytes significantly promoted the proliferation of porcine intramuscular preadipocytes, and also signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…have reported that Fatp1 promotes lipid accumulation in intramuscular preadipocytes. [ 60 ] Conversely, Qiu et al. have found that overexpression of Fatp1 inhibits lipid accumulation in QM‐7 (quail muscle) cells.…”
Section: Discussionmentioning
confidence: 99%
“…have reported that Fatp1 promotes lipid accumulation in intramuscular preadipocytes. [ 60 ] Conversely, Qiu et al. have found that overexpression of Fatp1 inhibits lipid accumulation in QM‐7 (quail muscle) cells.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that preadipocyte differentiation is a key factor affecting IMF deposition [ 36 ]. However, to date, only a few studies have identified genes that play important roles in porcine intramuscular preadipocyte differentiation, such as FABP1 [ 37 ], FABP4 , GPR39 [ 7 ], and CD36 [ 38 ]. The mechanisms by which intramuscular preadipocyte differentiation and fat deposition are regulated have also remained unclear in chicken.…”
Section: Discussionmentioning
confidence: 99%
“…A positive correlation between FATP1 and intramuscular fat deposition has been reported in pig [9]. Moreover, overexpression of FATP1 induced intramuscular preadipocyte proliferation and fat accumulation in pig [10]. FATP1 overexpression also significantly upregulated the expression levels of PPARγ, CEBPα, LPL, PLIN1, and FASN, and downregulated the expression of β-catenin.…”
Section: Introductionmentioning
confidence: 80%
“…FATP1 overexpression also significantly upregulated the expression levels of PPARγ, CEBPα, LPL, PLIN1, and FASN, and downregulated the expression of β-catenin. It was subsequently hypothesized that FATP1 might repress the Wnt,/β-catenin signaling pathway and stimulate adipogenesis in porcine intramuscular preadipocytes [10]. This hypothesis is supported by the results of RNA interference experiments in chicken.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation